Determination of formaldehyde from disposal of formaldehyde fixed biological specimen buried in soil - Musfiroh Jani; Shafiqah Shahirah Mohammad Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2021)
Biomedical waste specifically anatomical specimens and body parts will be incinerated by a local incineration facility. However, the incineration of formaldehyde fixed specimen from hospitals poses hazardous effect to human and environment due to an exposure of highly toxic gases such as dioxins and furans. In addition, this practise is considered as non-shariah compliance by Muslim community. Thus, a safer and shariah-compliance option to dispose anatomical specimens through deep burial has been introduced. The concern has been raised on the side effect of the formaldehyde treated specimen to the environment. Formaldehyde is used widely for preservation of surgical and anatomical specimens. The formaldehyde toxicity specifically on the soil, soil water, soil animals and plants should be considered after the burial of the anotamical specimens. Thus, the aim of this study was to investigate the side effect of formaldehyde on soil after the burial of formalin fixed specimen on the environment. In this study, the amount of soil elemental distribution and formaldehyde concentration of pre-burial and post-burial of biological specimen were evaluated by using Energy Dispersive X-Ray Fluorescence (EDXRF) and Ultraviolet-Visible Spectrophotometer instrument, respectively. For EDXRF analysis at Point C, soil elemental distribution after burial of dead biological specimens has higher concentration compared to before the burial. The concentration of formaldehyde at Point C was higher after the burial of dead biological specimen compared to before burial, which exceeds the tolerable concentration recommended by the World Health Organisation (WHO).